Influence of the Specific Position on The Final Result of The Match in Professional Basketball - Adrián Escudero-Tena; Ventura Rodríguez-Galán; Javier García-Rubio; Sergio J. Ibáñez, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Studies exploring performance indicators in basketball that characterize the result of the match are abundant. However, there are only a limited number of studies that carry out such analysis according to the specific positions of the players. The objective of this work is to characterize the differences by specific position between performance indicators of the matches of the 2017/18 season of the ACB League according to the result of the match. This study is a descriptive and observational research work that adopts a quantitative methodology for analysis. The study sample consists of 337 matches, in which the differences between game indicators were analyzed according to the specific position and the result of the match using the non-parametric tests U of Mann-Whitney and H of Kruskal-Wallis. The results show significant differences in the game indicators according to the specific position. The shots of three scored (d=.80) and taken (d=1.20), the total rebounds (d=.95) and offensive (d=.82), the assists (d=.93) and the dunks (d=.86) have a large effect size. In addition, there are significant differences by specific position in performance indicators based on the outcome of the match. It is concluded the performance indicators of the inside players are different from the outside ones and the players of the winning teams are more effective scorers, develop more assists, receive fewer blocks, dominate rebounds, receive more fouls and perform more dunks. These findings are of great interest to stakeholders in the basketball or sports industry, as they provide highly valuable information on the behavior of athletes in competition according to their specific position and the results of the match.